Human Gut Antibiotic Resistome and Progression of Diabetes. Issue 11 (10th February 2022) - Shuai, Menglei; Zhang, Guoqing; Zeng, Fang‐fang; Fu, Yuanqing; Liang, Xinxiu; Yuan, Ling; Xu, Fengzhe; Gou, Wanglong; Miao, Zelei; Jiang, Zengliang; Wang, Jia‐ting; Zhuo, Lai‐bao; et al.
Abstract: The antibiotic resistance crisis underlies globally increasing failures in treating deadly bacterial infections, largely due to the selection of antibiotic resistance genes (ARG) collection, known as the resistome, in human gut microbiota. So far, little is known about the relationship between gut antibiotic resistome and host metabolic disorders such as type 2 diabetes (T2D). Here, metagenomic landscape of gut antibiotic resistome is profiled in a large multiomics human cohort ( n = 1210). There is a significant overall shift in gut antibiotic resistome structure among healthy, prediabetes, and T2D groups. It is found that larger ARG diversity is associated with a higher risk of T2D. The novel diabetes ARG score is positively associated with glycemic traits. Longitudinal validation analysis confirms that the ARG score is associated with T2D progression, characterized by the change of insulin resistance. Collectively, the data describe the profiles of gut antibiotic resistome and support its close relationship with T2D progression. Abstract : Little is known about the relationship between gut antibiotic resistance genes (ARG) and diabetes. This study profiles the gut antibiotic resistome in a large human cohort ( n =1210). There is a significant overall shift in the ARG composition across healthy, prediabetes, and diabetes individuals. A novel diabetes‐ARG score is associated with diabetes progression, characterized by the alteration of insulin resistance.